(untitled) (Journal of history, 2023)
Abstract. The article describes the process of urbanization in the western region of the country in the XҮІІІ – early XX centuries in a historiographical context. Many research works on the history of cities of this period have been published, and special research has been carried out. The works of Russian travelers and researchers of the pre-revolutionary period were set out on the foundations, the territory, hydrographic and topographic features, the inhabitation and their legal and property status, and the economy. However, most of the works devoted to a special study of the history of the cities of Atyrau and Uralsk were published during the Soviet period. Their source base was wider, and the level of scholarly content was higher. At the same time, the authors of those works were methodologically guided by the political and ideological the principals of the totalitarian regime of the time. The views and conclusions of the authors are determined and evaluated in the context of a modern historical perspective through the analysis of works of various degrees, mainly dissertation and monographic, about cities in the region. The issues of the urbanization process of the XҮІІІ – early XX centuries that have not been fully researched and need to be studied are identified, and specific recommendations have been made. Key words: urbanization; cities; historiography; historical perspective; socio-economic development.